2014
DOI: 10.5194/acp-14-12499-2014
|View full text |Cite
|
Sign up to set email alerts
|

Variations of cloud condensation nuclei (CCN) and aerosol activity during fog–haze episode: a case study from Shanghai

Abstract: Abstract. Measurements of cloud condensation nuclei (CCN), condensation nuclei (CN) and aerosol chemical composition were performed simultaneously at an urban site in Shanghai from 6 to 9 November 2010. The variations of CCN number concentration (N CCN ) and aerosol activity (activated aerosol fraction, N CCN /N CN ) were examined during a fog-haze co-occurring event. Anthropogenic pollutants emitted from vehicles and unfavorable meteorological conditions such as low planetary boundary layer (PBL) height exert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 86 publications
(95 reference statements)
4
23
0
Order By: Relevance
“…It tends to reduce cloud droplet size and then suppress the wet precipitation in shallow and shortlived clouds (Lohmann and Feichter, 2005). Previous studies in Shanghai have found that CCN number concentration (N CCN ) and aerosol activity promotes effectively during the polluted periods (Leng et al, 2013(Leng et al, , 2014a. In north India, Ritesh et al (2007) observed a significant impact of winter haze on N CCN .…”
Section: Condensation Nuclei and Cloud Condensation Nucleimentioning
confidence: 98%
See 2 more Smart Citations
“…It tends to reduce cloud droplet size and then suppress the wet precipitation in shallow and shortlived clouds (Lohmann and Feichter, 2005). Previous studies in Shanghai have found that CCN number concentration (N CCN ) and aerosol activity promotes effectively during the polluted periods (Leng et al, 2013(Leng et al, , 2014a. In north India, Ritesh et al (2007) observed a significant impact of winter haze on N CCN .…”
Section: Condensation Nuclei and Cloud Condensation Nucleimentioning
confidence: 98%
“…When 80 % < RH < 90 %, the event is referred to as a complex of haze-fog co-occurring or transition (Leng et al, 2014a), and it is also classified as hazy episode in the present study. Figure 1a depicts the temporal variations of hourly PM 2.5 , PM 10 , atmospheric visibility and meteorological factors from 1 to 10 December 2013.…”
Section: Instrument and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of linearity between sulphate and nitrate in PM (2009 to 2011) Leng et al (2014a) Shanghai, CN Role of new particle formation on aerosol cloud condensation nuclei (CCN) activity (2012) Leng et al (2014b) Shanghai, CN Variations of CCN and aerosol activity during fog and haze events (2010) Makkonen et al (2014) Hyytiälä, FI Temporal cycles of NH 3 , HONO and HNO 3 at a boreal forest site (2010 to 2011) Rumsey et al (2014) North Carolina, US Performance study of the MARGA (US Environmental Protection Agency's Clean Air Status and Trends Network, CASTnet) (2010) Shi et al (2014) Shanghai, CN Investigation on PM 1 (variability, formation/dissociation, impacts on visibility) (2012) Zhou et al (2014) Shanghai, CN Measuring and modelling aerosols for haze events (2008 to 2010) a net radiometer CNR1 (Kipp&Zonen, The Netherlands) and a digital barometer (Vaisala, Germany), respectively.…”
Section: Site Description and Meteorological Parametersmentioning
confidence: 99%
“…Some studies (Ding & Liu, ; F. Niu, Li, et al, ) investigated the relations between fog and haze or aerosols but did not study the role of aerosols as cloud condensation nuclei. Therefore, we analyze fog‐aerosol relationships from the perspective of aerosol‐cloud interactions because fog can be viewed as near‐surface clouds (Leng et al, ; Zhu & Guo, ). This analysis can help to reveal how anthropogenic activities influence cloud physics.…”
Section: Introductionmentioning
confidence: 99%